A Feasibility study of SWIG Flavored Lagundi Tea - Caballes, Christian Frederick (College of Engineering, 2005)
Developmental studies and innovative advancements are the current focus of government institutions to address increasing problems in population and health care faced by the society. Contemplating on the focus of the government and gaining assistance from them, Swig: Flavored Lagundi Tea is conceived mainly to deal with the problem of increasing health risks due to development and congestion in the National Capital Region (NCR). Swig is considered for further study to follow the trend of changing lifestyle and shift to consumption of healthier food and beverages. With this, the feasibility of Swig in terms of market, technical, financial and social profitability is evaluated. Swig's initial target market is the NCR, the center of the Philippines' commerce. Moreover, it targets the fifteen to sixty age bracket because of their willingness to try the product and their exposure in using herbal products. Swig is packaged as a ready-to-drink (RTD) beverage, packed in PET bottles for ease of handling, resealability, and recyclability. It is available in four different flavors and mixed to suit the Filipino taste. Furthermore, Swig offers its medicinal advantage and its refreshing powers. Swig completes with C2 (URC), the top industry player of RTD teas, enjoying a market share of 42% along with the other RTD tea industry players in its first year. Also, it was projected that herbal products are to succeed in the global market, Swig is seen to have a large exportation potential. Furthermore, Swig sees increasing market as it gains popularity ans as it strengthens its marketing arm. A corresponding marketing and selling plan was conceived, to plan for the introduction of the product in the market. This covers the promotion and distribution costs for Swig, amounting to Php 246,870,000 for the first five years of operation. Swig will be manufactured in the Laguna Light Industry and Science Park located in Calamba, employing equipment used by similar sub-industries such as mixers and bottling lines. Furthermore, Swig's raw materials come from different suppliers, as evaluated using criteria such as total costs incurred and quality of delivered goods. In addition, in its pilot year, a total of 38 people will be employed, composed of both direct and administrative personnel, to produce Swig. Project financing will come from investors and a loan from IBank. The loan was projected to be 0.13 in its initial year. The return on assets is valued to be 0.15 in its first year and 0.45 at the end of the fifth year, while its payback period was projected to be equal to 0.27. In addition, a net present value (NPV) of Php 245,476,924.81 was obtained, by considering the firm's assets and liabilities. This value implies profitability of Swig in the industry. Aside from its financial profitability, the venture will also contribute to the society through its tax remittances, employment opportunities to locals, and stimulation of growth of other related industries.